2023
DOI: 10.3390/biology12050694
|View full text |Cite
|
Sign up to set email alerts
|

AIF1: Function and Connection with Inflammatory Diseases

Diego De Leon-Oliva,
Cielo Garcia-Montero,
Oscar Fraile-Martinez
et al.

Abstract: Macrophages are a type of immune cell distributed throughout all tissues of an organism. Allograft inflammatory factor 1 (AIF1) is a calcium-binding protein linked to the activation of macrophages. AIF1 is a key intracellular signaling molecule that participates in phagocytosis, membrane ruffling and F-actin polymerization. Moreover, it has several cell type-specific functions. AIF1 plays important roles in the development of several diseases: kidney disease, rheumatoid arthritis, cancer, cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 196 publications
0
10
0
Order By: Relevance
“…The AIF-1 gene is situated in the MHC class III region, close to the TNF-α, TNF-β, and NF-κB, complement cascade protein genes, and surface glycoprotein genes [ 27 ]. The relevance of AIF-1 in multiple diseases has been demonstrated broadly [ 35 ]. AIF-1 exert a critical immunomodulatory action, boosting the expression of many inflammatory mediators and favor macrophage and vascular smooth muscle cell proliferation and migration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AIF-1 gene is situated in the MHC class III region, close to the TNF-α, TNF-β, and NF-κB, complement cascade protein genes, and surface glycoprotein genes [ 27 ]. The relevance of AIF-1 in multiple diseases has been demonstrated broadly [ 35 ]. AIF-1 exert a critical immunomodulatory action, boosting the expression of many inflammatory mediators and favor macrophage and vascular smooth muscle cell proliferation and migration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that germ cells in L1;L2;A mice may be preparing to enter meiosis before ongoing apoptosis (Figure S2). Enrichment score expression of macrophage scavenger reporter 1 (MSR1/ CD204), a macrophage marker 55 and of allograft inflammatory factor 1 (AIF1), a protein involved in the activation of macrophages, T lymphocytes and dendritic cells, 56 was observed in the testis of L1;L2;A mice (Figure 5D) further confirming the presence of a robust immune response.…”
Section: The Expression Levels Of Leydig Cell and Germ Cell Genes Are...mentioning
confidence: 73%
“…AIF1 is known to induce the production of pro-inflammatory molecules, including the inflammatory factors IL-6 and TNF-α, and cause elevation of reactive oxygen species (ROS) ( 50 ). Furthermore, it has been shown that the role of AIF1 in macrophages is critical for maintaining their survival and promoting inflammatory activity ( 51 , 52 ). Based on these properties, it is reasonable to assume that there may be a positive correlation between AIF1 and AS, which is an immune-mediated disease characterized by chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%